Corneal Stromal Opacities Accompanied by Hyperopia and Irregular Astigmatism: Two-Step Technology of the Clinical Rehabilitation - I. A. Mushkova; N. V. Maychuk; R. A. Makarov; G. M. Chernakova (Oftalʹmologiâ)
Purpose: to identify risk factors for the development of asthenopic syndrome (AS) in patients with moderate to high myopia after keratorefractive surgery (KRS).Materials and methods. 122 patients (244 eyes) with medium and high myopia underwent a standard pre-operative examination of patients before KRS. The special methods of examinations were the study of reserves of relative accommodation (RRA) and the volume of absolute accommodation (VAA), and the accomodomography; the vision characteristics was determined on a four-point color test by E.B. Belostotsky, S.Y. Friedman at distances of 5.00 and 0.33 m, fusional reserves — with synoptophor. Patients survey was held with CISS questionnaire to detect the presence of AS.Results: There were no complications after KRS in all cases. Uncorrected visual acuity was the same or higher than maximal corrected before surgery in 1 week after KRS. Patents were divided into 2 groups according to results of CISS survey: 88% — without AS, 12% — with signs of AS. Retrospective analysis of pre-operative data of the patients with AS has shown that a combination of an absence of binocular vision with a pronounced decrease in fusion reserves, reserves of relative accommodation and volume of absolute accommodation is prognostically unfavorable factors in patients with myopia.Conclusion: All patients with moderate and high myopia have the refractive errors, there is no binocular vision in 12.3% patients. More significant errors of accommodation and binocular function were registered in patients with postoperative AS vs. patients without AS. Low fusion reserves and absence of binocular vision don’t allow to adopt for KRS results. This group of patients should be separated for pre-operative functional preparation.